"It was unusual but amazing": demand creation for PrEP among adolescents' men who have sex with men (MSM) and transgender women (TGW) in Brazil - Anderson Reis de Sousa; Luis Augusto Vasconcelos da Silva; Sandra Assis Brasil; Eliana Miura Zucchi; Dulce Aurélia de Souza Ferraz; Laio Magno; Alexandre Grangeiro; Ines Dourado (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: This study aimed to analyze the challenges in demand creation for participation in an HIV pre-exposure prophylaxis (PrEP) project in two Brazilian capitals. This qualitative study was conducted with men who have sex with men and transgender women aged 15 to 19 years who lived in two Brazilian state capitals. For this analysis, 27 semi-structured interviews carried out from 2019 to 2020 were evaluated by reflexive thematic content analysis. For participants, PrEP demand creation was essential for their interaction, mediation, bonding, and attachment and proved effective for PrEP acceptability and adherence. Adolescents' narratives showed that the strategies promoted HIV combination prevention, opened up opportunities for recruitment meetings, helped to negotiate with and convince individuals to use PrEP, strengthened peer education, and evoked a feeling of "being with" and "walking together" despite the challenges. Face-to-face or online interactions using social technologies played a crucial role in recruiting adolescents for the project, expanding knowledge on PrEP and other combination prevention strategies and access to health services and self-care.